2016
DOI: 10.1021/acs.jafc.6b00039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Immunoassay with Broad Specificity to Quinolone Drugs by Genetic Algorithm with Linear Assignment of Hypermolecular Alignment of Data Sets and Advanced Quantitative Structure–Activity Relationship Analysis

Abstract: A polyclonal antibody against the quinolone drug pazufloxacin (PAZ) but with surprisingly broad specificity was raised to simultaneously detect 24 quinolones (QNs). The developed competitive indirect enzyme-linked immunosorbent assay (ciELISA) exhibited limits of detection (LODs) for the 24 QNs ranging from 0.45 to 15.16 ng/mL, below the maximum residue levels (MRLs). To better understand the obtained broad specificity, a genetic algorithm with linear assignment of hypermolecular alignment of data sets (GALAHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The interaction between antigen and antibody of the immunoassay method was influenced by various factors. More and more studies have shown that the specificity of the antibody is of great significance for improving immunoassays . An antibody with high specificity (low cross‐reactivity [CR]) is suitable to be used in the immunoassay detecting a single compound, while an antibody with broad specificity (high CR) is suitable to be used in the immunoassay detecting multiple compounds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between antigen and antibody of the immunoassay method was influenced by various factors. More and more studies have shown that the specificity of the antibody is of great significance for improving immunoassays . An antibody with high specificity (low cross‐reactivity [CR]) is suitable to be used in the immunoassay detecting a single compound, while an antibody with broad specificity (high CR) is suitable to be used in the immunoassay detecting multiple compounds .…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have shown that the specificity of the antibody is of great significance for improving immunoassays. [9][10][11] An antibody with high specificity (low cross-reactivity [CR]) is suitable to be used in the immunoassay detecting a single compound, while an antibody with broad specificity (high CR) is suitable to be used in the immunoassay detecting multiple compounds. [12][13][14][15] However, because of the lack of knowledge about the antibody recognition and the ambiguous structure-activity relationship, artificial control of the specificity of the antibody remains a huge challenge.…”
mentioning
confidence: 99%
“…Quantitative regulations of immune recognition were recently formulated for monoclonal antibodies against ciprofloxacin (CIP) [23]. A potential of sarafloxacin [29], pazufloxacin [37], marbofloxacin, benfloxacin, norfloxacin, and pefloxacin [37] for broad-specific detection of FQs was also demonstrated. Polyclonal antibodies against clinafloxacin (CLI) were obtained and used for the immunoassay of FQs in milk [38].…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry not only provided a powerful method to explain the cross-reactivity but also became a useful tool to understand the hapten-antibody recognition mechanism in the absence of antibody physicochemical information. In particular, 2D-QSAR or 3D-QSAR methods, such as CoMSIA and CoMFA Contour, have been used in many studies to investigate the binding activities of polyclonal 14 , 18 , 19 and monoclonal 20 , 21 antibodies against structurally similar compounds. These methods, however, are only suitable for broad-specific antibodies that can recognize a large number of targets and are not suitable for antibodies that only recognize several compounds 22 .…”
Section: Introductionmentioning
confidence: 99%